60 Improved Peyronie's Disease Curvature Outcomes Using a More Aggressive Collagenase Technique. Issue 1 (1st April 2022) - Tyler, A; Green, B; Savage, J; Brearton, K; Burgon, H; Trost, L
ABSTRACT: Introduction: Since the FDA approval of Collagenase Clostridium Histolyticum (CCH) for the treatment of Peyronie's Disease (PD), several investigators have reported outcomes of CCH, with improvements ranging from approximately 15-30%. More recently, we reported improved results (49% mean improvement) when CCH was combined with RestoreX penile traction therapy (RxPTT). Since then, we have made additional modifications to create a more aggressive injection / traction protocol to further optimize outcomes. Objective: To report outcomes of a more aggressive CCH injection / traction protocol in men with PD. Methods: A prospective database has been maintained of all individuals undergoing CCH injections since 2014. Our CCH injection protocol has evolved from the one described in the IMPRESS trials to a more aggressive use of injections and manual and mechanical traction. Currently, the protocol consists of injecting 0.9 mg of CCH in 0.7 ml of saline into approximately 15-20 sites around the point of maximal curvature (pharmacologically-induced erection performed with the first injection of each series). Injections are only performed on subsequent days (not 2-3 days apart), and very aggressive (i.e. 10-15 lbs of force) modeling is performed with the 2nd injection. Patients are counseled to begin RestoreX traction at 24-48 hours after the 2nd injection for 30-60 minutes daily, and to continue aggressive manual modeling for at least the first week post injection. Penile wraps are applied for 5 days post injection. A descriptive analysis was subsequently performed to review outcomes. Results: A total of 320 men underwent at least 1 series of CCH and had baseline and follow-up curve assessment data available. Mean age was 55.8 (SD 10.4), with a mean PD duration of 27.8 months (SD 53) and a median baseline composite curvature of 64 degrees (IQR 45-80). Curvature improvements (most recent minus baseline) improved over time, correlating with increased injection experience and implementation of more aggressive traction protocols: 2014-2020 (20 degrees, 29% improvement) vs 2020-mid 2021 (27.8 degrees, 50%, p<0.001). When men were stratified by those who either completed 8 injections or indicated that they were satisfied with outcomes (n=147), median results were more pronounced: 2014-2017 (29% improvement), 2018 (38%), 2019 (47%), 2020-mid 2021 (59%), p<0.01. Conclusions: Progressive implementation of a more aggressive CCH injection protocol has resulted in improved curvature outcomes. Given the specialized nature of technique modifications described, these results would argue for a center-of-excellence model for CCH administration to achieve optimal outcomes. Disclosure: No